Kepemimpinan Kepala Sekolah dalam Meningkatkan Disiplin Kerja Guru di SMP Negeri 2 Kotamobagu - Fidya Tampoy; Sukarman Kamuli; Ariyanto Nggilu (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Teacher work discipline is a cornerstone of instructional effectiveness and the enhancement of educational quality. However, at SMP Negeri 2 Kotamobagu, a decline in motivation was observed among teachers nearing retirement, alongside a